ANALISIS KADAR KARBOHIDRAT DAN LEMAK PADA TEMPE BERBAHAN DASAR BIJI LAMUN (Enhalus acoroides) - Haslina Kole; Prelly Tuapattinaya; Theopilus Watuguly (Program Studi Pendidikan Biologi FKIP Unpatti, 2020)
Background: Seagrass (Enhalus Acoroides) is one of the most widely spread seagrass species in Indonesia and the seeds can be used by the community to be semi-processed product like Tempe (Fermented soyben). Another advantage possessed by Seagrass (Enhalus Acoroides) is that it has quite high nutrition. This research aimed to find out the carbohydrate and fat level on Tempe made from the fermentation of the seagrass seeds (Enhalus acoroides). Method: The analysis of the level of carbohydrate used by different method while the fat used Soxhlet method. Result: Based on the result of the research if the seagrass seeds been processed to be tempe, thus the carbohydrate and fat level was increased with the comparison of appropriate yeast. Conclusion: raw seagrass seeds if being processed to be tempe can increase the level of nutrition with the ppropriate amount of the yeast compared to consuming directly.